Faktor-Faktor yang Mempengaruhi Perilaku Nelayan Artisanal Dalam Pemanfaatan Sumberdaya Perikanan di Pantai Utara Provinsi Jawa Barat - Prihandoko, Prihandoko; Jahi, Amri; Gani, Darwis S.; Purnaba, I Gusti Putu; Adrianto, Luky; Tjitradjaja, Iwan (UI Scholars Hub, 2011)
This study aims to estimate accurately the behavior using the Theory of Planned Behavior perspective of artisanal fishermen in Indonesia, in the midst of life with the condition of degradation of marine resources are declining, absolute poverty faced by artisanal fishermen and the more complex issues of coastal resource use in Indonesia with a more diversity of stakeholders utilizing these resources. The population of artisanal fishermen in the northern coast of West Java Province 10,404. Techniques for sampling by cluster random sampling clusters with the number of household sample of 400 artisanal fishermen. Data was collected using a questionnaire interview further processed using the program structural equation model (SEM) and LISREL 8:54. The conclusion of this study were (1) Theory of planned behavior perspective can be used to view the intention to behave and conduct artisanal fishermen in the northern coast of West Java province, despite the possible existence of behavior that is done without the intention to behave (2) the coefficient of determination between the attitude variables, subjective norm, perceived behavior control to variable behavior intention at 0.40. These conditions indicate the existence of other variable factors of 60% outside variables that affect the intention of this study to behave. Meanwhile the influence of variables on behavior intention to behave by 0.51 indicates that it is not fully manifested the intention to behave in accordance with the behavior of fishermen in their fishing activities, (3) that explains the study's findings about the factors that influence the behavior of artisanal fishermen in the utilization fishery resources, can contribute to the activities of co-management of fisheries in Indonesia, especially in communities in the study area on the northern coast of West Java Province